Characteristics of Rural Users of Emergency Medical Services in Georgia: A Population-Based Study - Nannette Turner; Huey Chen; Liliana Morosanu (Georgia Southern University, 2016)
Background: Emergency medical services (EMS) are an essential part of health care. Appropriate information about EMS usage in rural areas will allow effective utilization of EMS resources for their intended purpose, and at the state level, drive the adoption of better EMS policies to ensure and maintain equitable access to these health services in rural areas. Methods: The present study, performed by analyzing data from the Georgia Emergency Medical Services Information System (GEMSIS), describes the population using EMS in rural Georgia. Distributions of rural EMS transports are reported, along with usage for selected population groups based on race, gender, age groups, and primary impressions recorded by emergency medical personnel (EMP). Results: The groups with the highest rates of EMS use were African Americans, females, and the elderly. In 2014, about twice as many African Americans used EMS as compared to Whites. Rural use of EMS increased with age, with the elderly having the highest percentage of users. About 31% of all transports were for emergency conditions; the remaining 69% were for non-emergencies. The most frequent health complaints were those for altered physical conditions and traumatic injuries. Conclusions: The findings of this study can guide decision in planning future services and ensuring appropriate access to EMS in rural Georgia.